Kontribusi Sistem Pendidikan Islam terhadap Transformasi Sosial, Ekonomi, dan Politik di Indonesia - Achmad Diny Hidayatullah (PT. PENERBIT TIGA MUTIARA, 2024)
Education is a basic human need. In Indonesia, the Islamic education system has made a significant contribution to social, economic, and political transformation. This is reflected in the increasing awareness of the community to send their children to madrasas and Islamic boarding schools and to practice religious teachings better. This reality shows that the Indonesian people, in various aspects of life, have felt the benefits of the Islamic education system. In the social, economic, and political realms, Islamic values ​​have a significant influence even though they are not yet fully optimal. Islamic education, as the main instrument, is expected to be able to bring about meaningful changes in these three fields. Education is an essential asset in improving the quality of human resources so that the values ​​and experiences of education based on Islam, individuals will continue to be inspired by Islamic values ​​throughout their lives. Through the implementation of an Islamic-based economic system, a social system based on Islam, and a political system that breathes the spirit of Islamic values, successful social, economic, and political transformation in Indonesia can be realized. Universal Islamic values ​​such as moderation, humanity, justice, deliberation, public benefit, unity, honesty, discipline, and tolerance are the basis for the development of various systems in Indonesia. If the Islamic education system is implemented well, it will be proven to make a unique contribution to the existing system. Friendly and loving Islam is the foundation of the social system in Indonesia.